The broad-spectrum caspase inhibitor Boc-Asp-CMK induces cell death in human leukaemia cells - Frydrych, Ivo; Mlejnek, Petr; Dolezel, Petr; Zoumpourlis, Vassilis; Krumpochova, Petra (Toxicology in vitro, 2008)
Synthetic caspase inhibitors and particularly broad-spectrum caspase inhibitors can prevent cells from death or at least slow down cell death process and abrogate some apoptotic hallmarks [Kitanaka, C., Kuchino, Y., 1999. Caspase-independent programmed cell death with necrotic morphology. Cell Death and Differentiation 6, 508-515]. However, not all synthetic caspase inhibitors diminish cell death. We have found that the broad-spectrum caspase inhibitor Boc-Asp-CMK induced cell death at micromolar concentrations in human leukaemia cells. Interestingly, low concentrations of Boc-Asp-CMK induced cell death with apoptotic hallmarks. Increasing concentrations of Boc-Asp-CMK led to necrotic cell death. The switch between apoptosis and necrosis seemed to depend upon the degree of inhibition of executioner caspases, including caspase-3/7 with Boc-Asp-CMK. Interestingly, caspase-3 processing was not inhibited even for the highest concentration of Boc-Asp-CMK used. We assume, that toxic properties of Boc-Asp-CMK can be attributed to the chloromethylketone residuum in its molecule, as its analogue Boc-Asp-FMK with fluoromethylketone residuum was more than 13 times less toxic. Our results further indicated that toxicity of Boc-Asp-CMK might arise from its interference with mitochondrial metabolism.
Keywords: viabilita buněk; Caspase 3; kaspasa 3; Cell Proliferation; vztah mezi dávkou a účinkem léčiva; Cell Survival; Enzyme Inhibitors; inhibitory kaspas; chloromethylketony aminokyselin; spotřeba kyslíku; Caspase Inhibitors; Oxygen Consumption; lidé; Humans; U937 Cells; apoptóza; proliferace buněk; Dose-Response Relationship, Drug; Amino Acid Chloromethyl Ketones; inhibitory enzymů; Apoptosis; U937 buňky